An empirical analysis on the price discovery function of iron ore futures market in China - Zhang, Fangqun; Li, Yangfu (Transactions on Economics, Business and Management Research, 2024)
The role of the iron ore futures market in price discovery is crucial when studying the future trend of China’s iron ore market. To promote the healthy and sustainable development of China’s iron ore futures market, this study collected data on the closing prices of the main chain of iron ore and China’s iron ore spot price index from December 2019 to December 2023 in the Dalian Commodity Futures Exchange. This paper aims to empirically analyze research methods and explore the mechanism behind price discovery in China’s iron ore futures market. Through detailed empirical research and in-depth analysis, this study reveals a close relationship between the volatility of iron ore futures and iron ore spot market prices, forming a long-term economic balance between them.